Preparation method for improving diaphragm rippled edge and battery weight impact
By using polyolefin resin, nano-inorganic fillers and antioxidants in the preparation of lithium-ion battery separators, and adopting a multi-step process, the problems of wavy edges of the separators and impact of the battery are solved, and the safety and performance of the battery are improved.
Patent Information
- Application Number
- CN202411876131.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
There are wave edge phenomena and battery heavy objects impact problems during the production process of existing lithium-ion battery separators, resulting in a decrease in battery charging and discharging efficiency and an increase in safety hazards.
By selecting polyolefin resin as the main raw material, adding nano-inorganic fillers and antioxidants, and using high-speed mixing, twin-screw extrusion, casting, stretching and heat setting treatment, a diaphragm with excellent mechanical strength and puncture resistance is prepared.
This method effectively reduces the wavy edge phenomenon on the surface of the diaphragm, improves the flatness and consistency of the diaphragm, enhances the safety and reliability of the battery, and can effectively prevent short-circuit accidents caused by heavy objects in the battery.
Smart Images

Figure CN119695392A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials for lithium-ion batteries, and in particular to a preparation method for improving the wave edge of a diaphragm and the impact of heavy objects on a battery. Background Art
[0002] With the rapid development of the new energy vehicle market and the country's emphasis on environmental protection policies, the demand for lithium batteries is also growing rapidly. As one of the four core components of lithium batteries, the diaphragm has a broad market prospect due to its high technical barriers and the market supply exceeding demand. At present, the commonly used lithium-ion battery diaphragms on the market are wet PE diaphragms and dry PP diaphragms. Among them, wet PE diaphragms dominate the market due to their excellent mechanical properties and chemical stability. However, there are some problems in the production process of wet PE diaphragms, such as wavy edge phenomenon and battery heavy object impact. Wavy edge refers to the uneven surface of the diaphragm, which affects the contact area between the diaphragm and the electrode, thereby affecting the battery's charge and discharge efficiency and cycle life. There are many reasons for the wavy edge, such as improper raw material ratio, production equipment failure, etc. These problems can be solved by optimizing the production process parameters. Battery heavy object impact refers to the damage caused by the battery being hit by external objects during transportation or use. This situation will cause internal short circuits in the battery, causing safety accidents such as fire or even explosion. In order to improve the safety of the battery, a more durable diaphragm material is needed.
[0003] The existing methods for improving the diaphragm wave edge and the battery heavy object impact are mainly achieved by adjusting the formula and processing technology, but these methods can only solve one of the problems and cannot take into account the requirements of both aspects at the same time. In addition, some methods also require additional equipment and processes, which increases the cost and complexity. In view of this, the present invention is specially proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method for improving the wavy edge of the diaphragm and the impact of heavy objects on the battery. The diaphragm produced by this preparation method has excellent mechanical strength and puncture resistance, which can effectively prevent short-circuit accidents when the battery is impacted by heavy objects. At the same time, it can also reduce the wavy edge phenomenon on the surface of the diaphragm, ensure the flatness and consistency of the diaphragm, and thus improve the overall performance of the battery.
[0005] The present invention is achieved in that:
[0006] In a first aspect, the present invention provides a preparation method for improving the diaphragm wave edge and the impact of heavy objects on the battery, comprising the following steps:
[0007] Raw material preparation: polyolefin resin is selected as the main raw material, and nano inorganic filler and antioxidant are added, the polyolefin resin is polyethylene, polypropylene or its copolymer, the nano inorganic filler is silicon dioxide, aluminum oxide or titanium dioxide nanoparticles with a particle size range of 10-100nm, and the addition amount of the antioxidant is 0.1%-1% of the mass of the polyolefin resin;
[0008] Mixed extrusion: After the raw materials are fully mixed in a high-speed mixer, they are added to a twin-screw extruder for melt blending and extrusion. The temperature of each zone of the twin-screw extruder is set as follows: Zone 1 150-160°C, Zone 2 160-170°C, Zone 3 170-180°C, Zone 4 180-190°C, Zone 5 190-200°C, and the screw speed is 200-300rpm;
[0009] Tape casting: The extruded material is cast onto a cooling roller through a casting head to form a diaphragm blank with uniform thickness. The temperature of the cooling roller is controlled at 20-30°C and the casting speed is 5-10m / min.
[0010] Stretching treatment: The diaphragm blank is first stretched longitudinally at a stretching multiple of 3-5 times and a stretching temperature of 80-100°C, and then stretched transversely at a stretching multiple of 4-6 times and a stretching temperature of 100-120°C;
[0011] Heat setting treatment: heat setting the stretched diaphragm at 130-150°C for 3-5 minutes;
[0012] Rolling and packaging: The heat-set diaphragm is rolled up and moisture-proof packaged to obtain the finished diaphragm.
[0013] Furthermore, the polyolefin resin is polyethylene, the nano inorganic filler is silicon dioxide nano particles with a particle size of 30 nm, and the added amount of the antioxidant is 0.3% of the weight of the polyethylene resin.
[0014] Furthermore, the polyolefin resin is polypropylene, the nano inorganic filler is aluminum oxide nano particles with a particle size of 50 nm, and the antioxidant is added in an amount of 0.5% of the mass of the polypropylene resin.
[0015] Furthermore, the polyolefin resin is a polyethylene-polypropylene copolymer, the nano inorganic filler is titanium dioxide nano particles with a particle size of 80 nm, and the amount of antioxidant added is 0.7% of the mass of the copolymer.
[0016] Furthermore, the temperature of each zone of the twin-screw extruder was set as follows: 155°C in zone 1, 165°C in zone 2, 175°C in zone 3, 185°C in zone 4, and 195°C in zone 5, the screw speed was 250rpm, the cooling roller temperature was 25°C, the casting speed was 8m / min, the longitudinal stretching multiple was 4 times, the stretching temperature was 90°C, the transverse stretching multiple was 5 times, the stretching temperature was 110°C, the heat setting temperature was 140°C, and the time was 4 minutes.
[0017] Furthermore, the temperature of each zone of the twin-screw extruder was set as follows: 158°C in zone 1, 168°C in zone 2, 178°C in zone 3, 188°C in zone 4, and 198°C in zone 5, the screw speed was 280rpm, the cooling roller temperature was 28°C, the casting speed was 9m / min, the longitudinal stretching ratio was 3.5 times, the stretching temperature was 95°C, the transverse stretching ratio was 4.5 times, the stretching temperature was 115°C, the heat setting temperature was 145°C, and the time was 3.5 minutes.
[0018] Furthermore, the temperature of each zone of the twin-screw extruder was set as follows: 152°C in zone 1, 162°C in zone 2, 172°C in zone 3, 182°C in zone 4, and 192°C in zone 5, the screw speed was 220rpm, the cooling roller temperature was 22°C, the casting speed was 6m / min, the longitudinal stretching ratio was 4.5 times, the stretching temperature was 98°C, the transverse stretching ratio was 5.5 times, the stretching temperature was 108°C, the heat setting temperature was 135°C, and the time was 4.5 minutes.
[0019] Furthermore, the temperature of each zone of the twin-screw extruder is set as: 160°C in zone 1, 170°C in zone 2, 180°C in zone 3, 190°C in zone 4, and 200°C in zone 5, the screw speed is 300rpm, the cooling roller temperature is 30°C, the casting speed is 10m / min, the longitudinal stretching multiple is 3 times, the stretching temperature is 100°C, the transverse stretching multiple is 6 times, the stretching temperature is 120°C, the heat setting temperature is 150°C, and the time is 5 minutes.
[0020] Furthermore, the temperature of each zone of the twin-screw extruder is set as: 150°C in zone 1, 160°C in zone 2, 170°C in zone 3, 180°C in zone 4, and 190°C in zone 5, the screw speed is 200rpm, the cooling roller temperature is 20°C, the casting speed is 5m / min, the longitudinal stretching multiple is 5 times, the stretching temperature is 80°C, the transverse stretching multiple is 4 times, the stretching temperature is 100°C, the heat setting temperature is 130°C, and the time is 3 minutes.
[0021] In a second aspect, the present invention also provides a battery separator prepared by the above preparation method.
[0022] Based on the solution provided by the present invention, the beneficial effects of the present invention are as follows:
[0023] The invention discloses a preparation method for improving the wave edge of a diaphragm and the impact of a heavy object on a battery, comprising the following steps: raw material preparation: selecting a polyolefin resin as a main raw material, and adding a nano inorganic filler and an antioxidant, wherein the polyolefin resin is polyethylene, polypropylene or a copolymer thereof, the nano inorganic filler is silicon dioxide, aluminum oxide or titanium dioxide nano particles with a particle size range of 10-100nm, and the added amount of the antioxidant is 0.1%-1% of the mass of the polyolefin resin; mixed extrusion: after the raw materials are fully mixed in a high-speed mixer, they are added into a twin-screw extruder for melt blending and extrusion, and the temperature of each zone of the twin-screw extruder is set as follows: 150-160°C for zone one, 160-170°C for zone two, 170-180°C for zone three, and 1 80-190℃, five zones 190-200℃, screw speed 200-300rpm; tape casting: the extruded material is cast onto the cooling roller through the tape casting head to form a diaphragm blank with uniform thickness, the temperature of the cooling roller is controlled at 20-30℃, and the tape casting speed is 5-10m / min; stretching treatment: the diaphragm blank is first stretched longitudinally, the stretching multiple is 3-5 times, the stretching temperature is 80-100℃, and then stretched transversely, the stretching multiple is 4-6 times, and the stretching temperature is 100-120℃; heat setting treatment: the stretched diaphragm is heat set at 130-150℃ for 3-5 minutes; winding and packaging: the heat-set diaphragm is rolled up and moisture-proof packaged to obtain a finished diaphragm. The present invention improves the mechanical strength and puncture resistance of the diaphragm by adding nano inorganic fillers and antioxidants, while also reducing the wavy edge phenomenon on the surface of the diaphragm, improving the consistency and flatness of the diaphragm, and thus improving the safety and reliability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The preparation flow chart of the present invention is shown. DETAILED DESCRIPTION
[0025] For the purpose of the following detailed description, it should be understood that the present invention may adopt various alternative changes and step sequences, unless expressly specified to the contrary. In addition, except in any operating examples, or otherwise indicated, all numbers representing the amount of ingredients used in the specification and claims should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters set forth in the following specification and the attached claims are approximate values that vary according to the desired performance to be obtained by the present invention. At least it is not intended to limit the application of the doctrine of equivalents to the scope of the claims, and each numerical parameter should at least be interpreted according to the number of reported significant figures and by applying ordinary rounding techniques.
[0026] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.
[0027] In addition, it should be understood that any numerical range described herein is intended to include all subranges subsumed therein. For example, a range of "1 to 10" is intended to include all subranges between (and including) the stated minimum value of 1 and the stated maximum value of 10, i.e., having a minimum value equal to or greater than 1 and a maximum value equal to or less than 10.
[0028] Example
[0029] Example 1
[0030] This embodiment provides a preparation method for improving the diaphragm wave edge and the impact of heavy objects on the battery, comprising the following steps:
[0031] (1) mixing polyethylene resin, silicon dioxide nanoparticles and antioxidant in a certain proportion to obtain a premix;
[0032] (2) adding the premixed material into a twin-screw extruder for melt blending and extrusion, the temperature of each zone of the twin-screw extruder was set as follows: zone 1 155°C, zone 2 165°C, zone 3 175°C, zone 4 185°C, zone 5 195°C, and the screw speed was 250 rpm;
[0033] (3) Casting the extruded material onto a cooling roller through a casting head to form a diaphragm blank with uniform thickness. The temperature of the cooling roller is controlled at 25° C. and the casting speed is 8 m / min.
[0034] (4) The diaphragm blank is firstly longitudinally stretched at a stretching ratio of 4 times and a stretching temperature of 90°C, and then transversely stretched at a stretching ratio of 5 times and a stretching temperature of 110°C;
[0035] (5) heat setting the stretched diaphragm at 140° C. for 4 minutes;
[0036] (6) The heat-set diaphragm is rolled up and moisture-proof packaged to obtain a finished diaphragm.
[0037] In this embodiment, the mass fraction of the polyethylene resin is 90%, the mass fraction of the silicon dioxide nanoparticles is 5%, and the mass fraction of the antioxidant is 5%.
[0038] Example 2
[0039] This embodiment provides a preparation method for improving the diaphragm wave edge and the impact of heavy objects on the battery, comprising the following steps:
[0040] (1) mixing polypropylene resin, aluminum oxide nanoparticles and antioxidant in a certain proportion to obtain a premix;
[0041] (2) adding the premixed material into a twin-screw extruder for melt blending and extrusion, the temperature of each zone of the twin-screw extruder was set as follows: zone 1 158°C, zone 2 168°C, zone 3 178°C, zone 4 188°C, zone 5 198°C, and the screw speed was 280 rpm;
[0042] (3) Casting the extruded material onto a cooling roller through a casting head to form a diaphragm blank with uniform thickness. The temperature of the cooling roller is controlled at 28° C. and the casting speed is 9 m / min.
[0043] (4) The diaphragm blank is firstly longitudinally stretched at a stretching ratio of 3.5 times and a stretching temperature of 95°C, and then transversely stretched at a stretching ratio of 4.5 times and a stretching temperature of 115°C;
[0044] (5) heat setting the stretched membrane at 145° C. for 3.5 minutes;
[0045] (6) The heat-set diaphragm is rolled up and moisture-proof packaged to obtain a finished diaphragm.
[0046] In this embodiment, the mass fraction of the polypropylene resin is 90%, the mass fraction of the aluminum oxide nanoparticles is 5%, and the mass fraction of the antioxidant is 5%.
[0047] Example 3
[0048] This embodiment provides a preparation method for improving the diaphragm wave edge and the impact of heavy objects on the battery, comprising the following steps:
[0049] (1) mixing polyethylene-polypropylene copolymer, titanium dioxide nanoparticles and antioxidant in a certain proportion to obtain a premix;
[0050] (2) adding the premixed material into a twin-screw extruder for melt blending and extrusion, the temperature of each zone of the twin-screw extruder was set as follows: zone 1 152°C, zone 2 162°C, zone 3 172°C, zone 4 182°C, zone 5 192°C, and the screw speed was 220 rpm;
[0051] (3) Casting the extruded material onto a cooling roller through a casting head to form a diaphragm blank with uniform thickness. The temperature of the cooling roller is controlled at 22° C. and the casting speed is 6 m / min.
[0052] (4) The diaphragm blank is firstly longitudinally stretched at a stretching ratio of 4.5 times and a stretching temperature of 98°C, and then transversely stretched at a stretching ratio of 5.5 times and a stretching temperature of 108°C;
[0053] (5) heat setting the stretched diaphragm at 135° C. for 4.5 minutes;
[0054] (6) The heat-set diaphragm is rolled up and moisture-proof packaged to obtain a finished diaphragm.
[0055] In this embodiment, the mass fraction of the polyethylene-polypropylene copolymer is 90%, the mass fraction of the titanium dioxide nanoparticles is 5%, and the mass fraction of the antioxidant is 5%.
[0056] Example 4
[0057] This embodiment provides a preparation method for improving the diaphragm wave edge and the impact of heavy objects on the battery, comprising the following steps:
[0058] (1) mixing polyethylene resin, silicon dioxide nanoparticles and antioxidant in a certain proportion to obtain a premix;
[0059] (2) adding the premixed material into a twin-screw extruder for melt blending and extrusion, the temperature of each zone of the twin-screw extruder is set as follows: 160° C. for zone 1, 170° C. for zone 2, 180° C. for zone 3, 190° C. for zone 4, and 200° C. for zone 5, and the screw speed is 300 rpm;
[0060] (3) Casting the extruded material onto a cooling roller through a casting head to form a diaphragm blank with uniform thickness. The temperature of the cooling roller is controlled at 30° C. and the casting speed is 10 m / min.
[0061] (4) The diaphragm blank is firstly longitudinally stretched at a stretching ratio of 3 times and a stretching temperature of 100°C, and then transversely stretched at a stretching ratio of 6 times and a stretching temperature of 120°C;
[0062] (5) heat setting the stretched diaphragm at 150° C. for 5 minutes;
[0063] (6) The heat-set diaphragm is rolled up and moisture-proof packaged to obtain a finished diaphragm.
[0064] In this embodiment, the mass fraction of the polyethylene resin is 90%, the mass fraction of the silicon dioxide nanoparticles is 5%, and the mass fraction of the antioxidant is 5%.
[0065] Example 5
[0066] This embodiment provides a preparation method for improving the diaphragm wave edge and the impact of heavy objects on the battery, comprising the following steps:
[0067] (1) mixing polypropylene resin, aluminum oxide nanoparticles and antioxidant in a certain proportion to obtain a premix;
[0068] (2) adding the premixed material into a twin-screw extruder for melt blending and extrusion, the temperature of each zone of the twin-screw extruder is set as follows: 150° C. for zone 1, 160° C. for zone 2, 170° C. for zone 3, 180° C. for zone 4, and 190° C. for zone 5, and the screw speed is 200 rpm;
[0069] (3) Casting the extruded material onto a cooling roller through a casting head to form a diaphragm blank with uniform thickness. The temperature of the cooling roller is controlled at 20° C. and the casting speed is 5 m / min.
[0070] (4) The diaphragm blank is firstly longitudinally stretched at a stretching ratio of 5 times and a stretching temperature of 80°C, and then transversely stretched at a stretching ratio of 4 times and a stretching temperature of 100°C;
[0071] (5) heat setting the stretched diaphragm at 130° C. for 3 minutes;
[0072] (6) The heat-set diaphragm is rolled up and moisture-proof packaged to obtain a finished diaphragm.
[0073] In this embodiment, the mass fraction of the polypropylene resin is 90%, the mass fraction of the aluminum oxide nanoparticles is 5%, and the mass fraction of the antioxidant is 5%.
[0074] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A preparation method for improving the wave edge of the diaphragm and the impact of heavy objects on the battery, characterized in that: The following steps are involved: Raw material preparation: polyolefin resin is selected as the main raw material, and nano inorganic filler and antioxidant are added, the polyolefin resin is polyethylene, polypropylene or its copolymer, the nano inorganic filler is silicon dioxide, aluminum oxide or titanium dioxide nanoparticles with a particle size range of 10-100nm, and the added amount of the antioxidant is 0.1%-1% of the mass of the polyolefin resin; mixed extrusion: the raw materials are fully mixed in a high-speed mixer, and then added to a twin-screw extruder for melt blending and extrusion. The temperature of each zone of the twin-screw extruder is set as follows: 150-160°C for zone 1, 160-170°C for zone 2, 170-180°C for zone 3, 180-190°C for zone 4, and 190-200°C for zone 5 , the screw speed is 200-300rpm; tape casting: the extruded material is cast onto the cooling roller through the tape casting head to form a diaphragm blank with uniform thickness, the temperature of the cooling roller is controlled at 20-30℃, and the tape casting speed is 5-10m / min; stretching treatment: the diaphragm blank is first stretched longitudinally, the stretching multiple is 3-5 times, the stretching temperature is 80-100℃, and then stretched transversely, the stretching multiple is 4-6 times, and the stretching temperature is 100-120℃; heat setting treatment: the stretched diaphragm is heat-set at 130-150℃ for 3-5 minutes; winding and packaging: the heat-set diaphragm is rolled up and moisture-proof packaged to obtain a finished diaphragm.
2. The preparation method according to claim 1, characterized in that: The polyolefin resin is polyethylene, the nano inorganic filler is silicon dioxide nano particles with a particle size of 30nm, and the added amount of the antioxidant is 0.3% of the weight of the polyethylene resin.
3. The preparation method according to claim 1, characterized in that: The polyolefin resin is polypropylene, the nano inorganic filler is aluminum oxide nano particles with a particle size of 50nm, and the added amount of the antioxidant is 0.5% of the mass of the polypropylene resin.
4. The preparation method according to claim 1, characterized in that: The polyolefin resin is polyethylene-polypropylene copolymer, the nano inorganic filler is titanium dioxide nano particles with a particle size of 80nm, and the added amount of the antioxidant is 0.7% of the mass of the copolymer.
5. The preparation method according to claim 1, characterized in that: The temperature settings of each zone of the twin-screw extruder are: 155°C in zone 1, 165°C in zone 2, 175°C in zone 3, 185°C in zone 4, and 195°C in zone 5. The screw speed is 250rpm, the cooling roller temperature is 25°C, the casting speed is 8m / min, the longitudinal stretching multiple is 4 times, the stretching temperature is 90°C, the transverse stretching multiple is 5 times, the stretching temperature is 110°C, the heat setting temperature is 140°C, and the time is 4 minutes.
6. The preparation method according to claim 1, characterized in that: The temperature settings of each zone of the twin-screw extruder are: 158°C in zone 1, 168°C in zone 2, 178°C in zone 3, 188°C in zone 4, and 198°C in zone 5. The screw speed is 280rpm, the cooling roller temperature is 28°C, the casting speed is 9m / min, the longitudinal stretching multiple is 3.5 times, the stretching temperature is 95°C, the transverse stretching multiple is 4.5 times, the stretching temperature is 115°C, the heat setting temperature is 145°C, and the time is 3.5 minutes.
7. The preparation method according to claim 1, characterized in that: The temperature settings of each zone of the twin-screw extruder are: 152°C in zone 1, 162°C in zone 2, 172°C in zone 3, 182°C in zone 4, and 192°C in zone 5. The screw speed is 220rpm, the cooling roller temperature is 22°C, the casting speed is 6m / min, the longitudinal stretching multiple is 4.5 times, the stretching temperature is 98°C, the transverse stretching multiple is 5.5 times, the stretching temperature is 108°C, the heat setting temperature is 135°C, and the time is 4.5 minutes.
8. The preparation method according to claim 1, characterized in that: The temperature settings of each zone of the twin-screw extruder are: 160°C in zone 1, 170°C in zone 2, 180°C in zone 3, 190°C in zone 4, and 200°C in zone 5. The screw speed is 300rpm, the cooling roller temperature is 30°C, the casting speed is 10m / min, the longitudinal stretching multiple is 3 times, the stretching temperature is 100°C, the transverse stretching multiple is 6 times, the stretching temperature is 120°C, the heat setting temperature is 150°C, and the time is 5 minutes.
9. The preparation method according to claim 1, characterized in that: The temperature settings of each zone of the twin-screw extruder are: 150°C in zone 1, 160°C in zone 2, 170°C in zone 3, 180°C in zone 4, and 190°C in zone 5, the screw speed is 200rpm, the cooling roller temperature is 20°C, the casting speed is 5m / min, the longitudinal stretching multiple is 5 times, the stretching temperature is 80°C, the transverse stretching multiple is 4 times, the stretching temperature is 100°C, the heat setting temperature is 130°C, and the time is 3 minutes.
10. A battery separator prepared by the preparation method according to any one of claims 1 to 9.